A multi‐institutional study of salivary gland cytopathology: Application of the Milan System for Reporting Salivary Gland Cytopathology in Japan. Issue 1 (3rd September 2021) - Higuchi, Kayoko; Urano, Makoto; Akiba, Jun; Nogami, Miwako; Hirata, Yukiya; Zukeran, Yoko; Moriyoshi, Koki; Tada, Yuichiro; Fukushima, Mana; Obayashi, Mariko; Sakamoto, Shinnichi; Kuraoka, Kazuya; et al.
Abstract : Background: The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) is a risk‐stratification reporting system that was introduced in 2018. The objective of this multi‐institutional study was to evaluate the utility of the MSRSGC in Japan. Methods: In total, 1608 fine‐needle aspiration samples with matching histologic diagnoses were retrieved from 12 large institutions in Japan. The diagnostic categories of the MSRSGC were assigned prospectively or retrospectively, and the results were compared with the histologic diagnoses. Results: The cases were classified as follows: nondiagnostic, 18.1%; non‐neoplastic, 4.1%; atypia of undetermined significance, 11.5%; neoplasm‐benign, 43.7%; salivary gland neoplasm of uncertain malignant potential, 9.6%; suspicious for malignancy, 3.6%; and malignant, 9.4%. The risk of neoplasm and the risk of malignancy in each MSRSGC category were as follows: nondiagnostic, 72.9% and 13.4%, respectively; non‐neoplastic, 15.2% and 9.1%, respectively; atypia of undetermined significance, 77.9% and 24.9%, respectively; neoplasm‐benign, 99% and 1.8%, respectively; salivary gland neoplasm of uncertain malignant potential, 94.8% and 37%, respectively; suspicious for malignancy, 100% and 89.7%, respectively; and malignant, 100% and 99.3%, respectively. The accuracy of the MSRSGC for diagnosing neoplasms was 97.8%, and its accuracy for diagnosing malignancy was 97.3%. Institutions that used Romanowsky‐stained preparations had lower nondiagnostic rates and lower risks of neoplasm and malignancy in the non‐neoplastic category. Conclusions: The MSRSGC is useful for risk stratification and quality control. Widespread use of the MSRSGC would improve the accuracy of salivary gland cytology and lead to better patient care in Japan. Abstract : This is the first multi‐institutional study of a large‐scale application of the Milan System for Reporting Salivary Gland Cytopathology in Japan. It demonstrates the usefulness of the Milan system in the diagnosis of salivary gland lesions and for the quality control of salivary gland cytology results.